Sintesis dan Karakterisasi Sifat Keasaman dan Morfologi Katalis K-Co-Mo/ZAAEF - Kasimir Sarifudin; Maria Erfina Karfona (Pendidikan MIPA Universitas Nusa Cendana, 2025)
This research intends to determine variations in acidity and surface morphology of the catalyst while employing different quantities of Mo and Co. Natural zeolite from Ende-Flores was activated via a hydrothermal method, accompanied by chemical activation utilizing HF, HCl, and NH₄Cl. The K-Co-Mo/ZAAEF catalyst was synthesized by the co-impregnation method utilizing solutions of CoCl₂∙6H₂O, (NH₄)₆Mo₇O₂₄∙4H₂O, and K₂CO₃ as precursor compounds for the metals K, Co, and Mo. The catalyst activation included calcination, oxidation, and reduction procedures at 500 °C, utilizing nitrogen, oxygen, and hydrogen gases, respectively. The catalyst surface acidity was measured using the gravimetric technique with pyridine vapor. The research findings indicate that the acidity of the catalyst varies with varied molar ratios of Mo/Co precursor metals. The catalyst exhibited an increase with varied molar ratios of Mo/Co precursor metals from 0 to 0.6, whereas those with molar ratios over 0.6 showed decreasing values. The K-Co-Mo0.6/ZAAEF catalyst has the highest surface acidity at 0.0946 mmol/gram. The findings from functional group identification via FT-IR indicate that the catalyst comprises Lewis and Brønsted acid sites. A modest quantity of Mo precursor metal, with a Mo to Co precursor metal ratio of 0.3-0.6, yields a catalyst exhibiting an absorption band for Brønsted acid sites; conversely, a higher quantity of Mo precursor metal does not produce this absorption band. Microscopic test results indicate that the surface morphology of the catalysts varies with differing quantities of Mo/Co precursor metals. The K-Co-Mo0.6/ZAAEF catalyst has a well-dispersed surface shape characterized by a more homogeneous particle dispersion relative to the other catalysts.